Evaluation of the Financial Performance of Islamic Banking in Indonesia Using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) Method and the Islamicity Performance Index (IPI) Period 2019 - 2023 - Zahri, Ardiman; Setiawan, Romi Adetio; Afrianty, Nonie (Jurnal Iqtisaduna, 2025)
This study aims to evaluate the financial performance of Islamic banking in Indonesia for the 2019–2023 period using two main approaches, namely the Risk Profile, Good Corporate Governance, Earnings, Capital (RGEC), and Islamicity Performance Index (IPI) methods. This research method uses a quantitative descriptive approach with secondary data from the annual financial reports of seven Islamic Commercial Banks registered with the OJK. The analysis was carried out on various financial ratios to assess risk, profitability, capital, and the suitability of bank operations with Sharia principles. The study's results indicate that, in general, the Islamic Commercial Banks' financial performance is in the good category according to the RGEC approach. However, several indicators, such as BOPO and ROA, still need improvement. Meanwhile, through the IPI approach, it was found that although there is still an imbalance in the distribution of income and zakat, most banks have shown sufficient commitment to the principles of Islamic finance.